METODE PENETAPAN DAN PERHITUNGAN ZAKAT (‘ARUDZ AL-TIJARA) MENURUT FIQH DAN BADAN AMIL ZAKAT NASIONAL (BAZNAS) - Zalia, Siti (Universitas Islam Negeri Raden Fatah Palembang, 2016)
Scene study of fiqh of zakat is already widely studied by several researchers and scholars from generation to generation from the Prophet era until now. Zakat issues commonly found in classical literature that developed up to this time, either in the form of scientific publications and other scientific books. Determination and calculation of zakat 'arudz al-Tijara according to fiqh is related to the setting haul and nishab while according to the National Zakat Agency is spending zakat calculation' arudz al-Tijara on the basis of the haul and nishab. This article will explore methods of determination and calculation of zakat according to fiqh expert and by Badan Amil Zakat in Indonesia. ملخص: وفيما يتعلق فقه الزكاة وبالفعل درس على نطاق واسع من قبل العديد من العلماء والباحثين والعلماء من جيل إلى جيل من عهد النبي حتى الآن. قضايا الزكاة هو شائع في الأدب الكلاسيكي والأدب التي وضعت حتى هذا الوقت، إما في شكل المطبوعات العلمية والكتب العلمية الأخرى. تقرير وحساب زكاة العروض تجارة-يرتبط وفقا لفقه لمسافات إعداد و حين وفقا لوكالة الزكاة الوطنية تنفق حساب الزكاة تجارة على أساس المدى وهذه المادة سوف تستكشف طرق تحديد وحساب الزكاة وفقا لفقه وبادان العامل الزكاة في اندونيسيا.